Is masticatory performance affected after a unilateral condylar fracture? A cross‐sectional study. (18th July 2018) - Rozeboom, Antoinette; Speksnijder, Caroline; Dubois, Leander; Lobbezoo, Frank; Koutris, Michail; de Lange, Jan
Summary: Background: Mandibular fractures, especially condylar fractures, are one of the most common facial fractures. Trauma to this region could possibly compromise masticatory performance, which is a vital function for humans. Objective: To objectively determine masticatory performance (Mixing Ability Test; MAT) in patients treated for a unilateral condylar fracture, thereby comparing patients in open and closed treatment groups, and assessing whether there is a positive relationship between this performance and subjective mandibular function (Mandibular Functional Impairment Questionnaire; MFIQ). Methods: Fifty‐eight patients were enrolled in a cross‐sectional study and examined on an additional appointment at least 1 year after trauma, during which the patients performed the MAT and completed the MFIQ. The Spearman test was used to assess the correlation between the Mixing Ability Index (MAI) and the MFIQ score. A linear regression was used to explore the effects of different factors on the MAI. Results: The correlation between objective masticatory performance and the subjective mandibular function was positive ( r = 0.250; P = 0.033). Better masticatory performance was observed in patients who were male, received physiotherapy, had no other mandibular fractures and/or had satisfactory self‐perceived occlusion. No significant difference in the MAI was found between the open and closed treatment groups. Conclusion: Independent of the chosen treatment, at least 1 year after treatment, individuals who experienced a unilateral fracture of the mandibular condyle exhibit masticatory capacity comparable with that of individuals who have not suffered such injuries.